Mast Cells are Important Modifiers of Autoimmune Disease: With so Much Evidence, Why is There Still Controversy? - Brown, Melissa A.; Hatfield, Julianne K. (Frontiers in Immunology, 2012)
There is abundant evidence that mast cells are active participants in events that mediate tissue damage in autoimmune disease. Disease-associated increases in mast cell numbers accompanied by mast cell degranulation and elaboration of numerous mast cell mediators at sites of inflammation are commonly observed in many human autoimmune diseases including multiple sclerosis, rheumatoid arthritis and bullous pemphigoid. In animal models, treatment with mast cell stabilizing drugs or mast cell ablation can result in diminished disease. A variety of receptors including those engaged by antibody, complement, pathogens and intrinsic danger signals are implicated in mast cell activation in disease. Similar to their role as first responders in infection settings, mast cells likely orchestrate early recruitment of immune cells, including neutrophils, to the sites of autoimmune destruction. This co-localization promotes cellular crosstalk and activation and results in the amplification of the local inflammatory response thereby promoting and sustaining tissue damage. Despite the evidence, there is still a debate regarding the relative role of mast cells in these processes. However, by definition, mast cells can only act as accessory cells to the self-reactive T and/or antibody driven autoimmune responses. Thus, when evaluating mast cell involvement using existing and somewhat imperfect animal models of disease, their importance is sometimes obscured. However, these potent immune cells are undoubtedly major contributors to autoimmunity and should be considered as important targets for therapeutic disease intervention.